Pertimbangan Perkara Pemeliharaan Anak di Pengadilan Agama Manado - Jamal, Ridwan; Bukido, Rosdalina; Yasin, Yasin (Institut Agama Islam Negeri Curup, 2021)
This research aims to analyze the consideration of judge in giving the case decision on child custody (hadanah) as well as upholding the decision of religious court in Manado concerning accountability of child custody. This type of research is field research which is qualitative and used descriptive analysis research method. Whilist the approach used in this research is empirical law method. The result of research shows that the child custody decided by religious court in Manado is persuasive, namely through sociological considerations and considerations of benefit (maslahat), so that it will not harm the child or cause family conflict. Various problems in Manado religious court due to the lack of responsibility, cherish and education from parents to their children became the judge’s consideration in deciding the case. Therefore, the judges must be careful in making decision. In addition, in resolving the issue of hadhanah, not only formal rules must be mentioned, but also legal values, social principles, religious principles, the environment that will be given to parents concerning hadhanah and some other aspects must be considered, especially about the future of their children.